Alleviation of proton toxicity by nitrate uptake specifically depends on nitrate transporter 1.1 in Arabidopsis. Issue 1 (11th February 2016) - Fang, Xian Zhi; Tian, Wen Hao; Liu, Xing Xing; Lin, Xian Yong; Jin, Chong Wei; Zheng, Shao Jian
Summary: Protons in acid soil are highly rhizotoxic to plants, but the mechanism of tolerance of plants to protons is largely unknown. Nitrate uptake by root cells is accompanied by the uptake of protons. Therefore, nitrate uptake transporters (NRTs) may be involved in plant tolerance to proton toxicity. We investigated the root nitrate uptake response to proton stress in Arabidopsis and its association with proton tolerance using NRT‐related mutants and pharmacological methods. Lack of NRT1.1 in knockout nrt1.1 mutants led to impaired proton tolerance in nitrate‐sufficient growth medium, whereas no difference was seen between wild‐type plants and NRT1.2‐, NRT2.1‐, NRT2.2‐, and NRT2.4‐null mutants. Another nrt1.1 point mutant, which is defective in nitrate uptake but has a normal nitrate‐sensing function, also had impaired proton tolerance compared with the wild‐type plant. Furthermore, proton stress induced NRT1.1‐mediated nitrate uptake. These results indicate that NRT1.1‐conferred proton tolerance depends on nitrate uptake activity. In addition, the rooting medium was alkalified by wild‐type plants, but not by knockout nrt1.1 mutants, and in pH‐buffered medium, there were no differences in proton tolerance between wild‐type plants and knockout nrt1.1 mutants. We conclude that NRT1.1‐mediated nitrate uptake plays a crucial role in plant proton tolerance by alkalifying the rhizosphere.